USING PICTURE SERIES FOR COOPERATIVE LEARNING TO IMPROVE STUDENT’S SPEAKING ABILITY - Ika Nuriyanti (PROJECT (Professional Journal of English Education), 2023)
Cooperative learning is a way of teaching methods in which the students work together with their friend in small groups for helping each other by giving idea and sharing in learning a certain lesson material. Picture series is one of media in teaching English, picture series is a type of media that is very interesting to study especially the various pictures. Speaking is one of the skills that the students should mastered in learning English, speaking is a complex skill because at least it is concerned with components of pronunciation, grammar, vocabulary and fluency. The research, uses classroom action research (CAR) design through two cycles. Each cycle has one meeting and consist of four stages: first is planning, the second is acting, the third is observing, and the last is reflecting. The research was conducted in eleventh grade at SMA Islam Batu - Malang. Based on the research of test in cycle I and cycle II, the average score of  preliminary study is 47 and the class percentage that got by students is 26%. The mean score in cycle I is 60 and the class percentage that got by students 36%. The mean score in cycle II is 62 and the class percentage that got by students is 73%. It mean that the students always have improvement from preliminary, cycle I until cycle II.Based on the result, the researcher thinks that by using picture series can improve speaking ability for student. The students’ can relax if learn with cooperative learning with picture series because the students’ more be enjoy on teaching and learning process. The implementation of cooperative learning method also can use for teaching speaking. Keywords:  Cooperative Learning; Picture Series; Speaking